Perbandingan Kadar High Density Lipoprotein dan Indeks Massa Tubuh antara Akseptor KB Pil Kombinasi dengan Depo Medroksiprogesteron - Helti Lestari Sitinjak; Rauza Sukma Rita; Yusrawati . . (Media Kesehatan Masyarakat Indonesia, 2019)
More than six million women worldwide use contraceptive injection and the popular contraceptive methodused is contraceptive pill. This is due to one of the side effects of combination pill contraception is to increasetriglyceride levels, total cholesterol and changes in carbohydrate metabolism while the side effects of DepotMedroxyprogesterone Acetate are irregular menstruation/amenorrhea, changes in body weight and lipid changes.This research is an observational with cross sectional comparative approach to 36 combination pill acceptorand 36 Depot Medroxyprogesterone Acetate acceptor. This study was conducted ini the area of Andalas andLubuk Buaya Health Center. The sampling method used in this research was simple random sampling method.The analysis was used T-Independent test and chi square test. The results showed that High Density Lipoproteinleves Depot Medroxyprogesterone Acetate (63,97±12,75 mg/dl) vs combined contraceptive pill (60,06±15,57 mg/dl), p=0,25 and Body Mass Index levels of overweight combined contraceptive pill acceptor higher than DepotMedroxyprogesterone Acetate (p=0,08). Results of this study concluded was that there were no significantdifferences in the levels of High Density Lipoprotein and Body Mass Index between combined contraceptive pilland Depot Medroxyprogesterone Acetate acceptor